2005
DOI: 10.1148/radiol.2341031596
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging of the Wrist: Comparison between 1.5- and 3-T MR Imaging—Preliminary Experience

Abstract: Institutional review board approval and informed consent were obtained from 25 healthy volunteers and 15 consecutive patients with chronic wrist pain or suspected carpal mass, and 1.5- and 3-T magnetic resonance (MR) imaging of the wrist was prospectively performed with comparable sequence parameters and surface coils of the same geometric design. Imaging protocols at both field strengths included a T1-weighted spin-echo sequence, two intermediate-weighted fast SE sequences with different echo times and with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
112
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(118 citation statements)
references
References 32 publications
4
112
0
2
Order By: Relevance
“…Next to neuromuscular disorders, malignancies, infections and hematomas and ruptures of the musculoskeletal system can also be detected with ultrasound [7,9,10,24]. Currently, ultrasound is widely available and ultrasound techniques have further improved, resulting in display of muscle tissue with resolutions up to 0.1 mm [8], which is higher than the resolution that can be achieved with for example 3 Tesla Magnetic Resonance Imaging (MRI), which has a resolution up to 0.2 x 0.2 x 1.0 mm [38]. This article provides insight in the use of muscle ultrasound in the display of healthy and diseased muscle.…”
Section: Ultrasound Of Normal Muscle Tissue 2 Muscle Ultrasound In Nmentioning
confidence: 99%
“…Next to neuromuscular disorders, malignancies, infections and hematomas and ruptures of the musculoskeletal system can also be detected with ultrasound [7,9,10,24]. Currently, ultrasound is widely available and ultrasound techniques have further improved, resulting in display of muscle tissue with resolutions up to 0.1 mm [8], which is higher than the resolution that can be achieved with for example 3 Tesla Magnetic Resonance Imaging (MRI), which has a resolution up to 0.2 x 0.2 x 1.0 mm [38]. This article provides insight in the use of muscle ultrasound in the display of healthy and diseased muscle.…”
Section: Ultrasound Of Normal Muscle Tissue 2 Muscle Ultrasound In Nmentioning
confidence: 99%
“…For the intrinsic small and thin structures of the TFCC, high field MR scanner e.g., 3 Tesla MR scanner is ideally used to acquire a high spatial, high contrast imaging data (1,18).…”
Section: Mri Techniquementioning
confidence: 99%
“…It is noteworthy that most of the MRI studies reported so far have been conducted using a conventional magnetic field, i.e., 1.5T but a few studies have clearly indicated that MRI investigations at higher field, e.g., 3T could provide a better signal/noise ratio and a more accurate identification of certain anatomical structures [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%